Rebranding dalam Menciptakan Citra Baru dan Meningkatkan Loyalitas Pelanggan (Studi pada Nonaria Keik menjadi Nonaria Artisan) - Widya Darma Sasabila; Eraskaita Ginting; Muslimin Ritonga (LPPM Universitas Bina Sarana Informatika, 2025)
The development of modern lifestyles encourages culinary MSMEs to adapt through rebranding to strengthen brand image and customer loyalty. This study aims to analyze the rebranding stages and strategies implemented after the rebranding of the Nonaria Keik MSME which transformed into Nonaria Artisan Bakery & Café. The theoretical basis used is Brand Equity according to Aaker which includes brand awareness, brand association, perceived quality, and brand loyalty. This study uses a descriptive qualitative method with interview, observation, and documentation techniques. The results show that the stages of repositioning, renaming, redesign, and relaunching followed by consistent brand communication strategies, digital promotions, customer relationship management, and improving service quality can increase brand Equity and customer loyalty. Rebranding has proven effective in building a professional brand image and long-term loyalty.